Oxidative Metabolism in Brain Ischemia and Preconditioning: Two Sides of the Same Coin - Elena D'Apolito; Maria Josè Sisalli; Michele Tufano; Lucio Annunziato; Antonella Scorziello (MDPI AG, 2024)
Brain ischemia is one of the major causes of chronic disability and death worldwide. It is related to insufficient blood supply to cerebral tissue, which induces irreversible or reversible intracellular effects depending on the time and intensity of the ischemic event. Indeed, neuronal function may be restored in some conditions, such as transient ischemic attack (TIA), which may be responsible for protecting against a subsequent lethal ischemic insult. It is well known that the brain requires high levels of oxygen and glucose to ensure cellular metabolism and energy production and that damage caused by oxygen impairment is tightly related to the brain's low antioxidant capacity. Oxygen is a key player in mitochondrial oxidative phosphorylation (OXPHOS), during which reactive oxygen species (ROS) synthesis can occur as a physiological side-product of the process. Indeed, besides producing adenosine triphosphate (ATP) under normal physiological conditions, mitochondria are the primary source of ROS within the cell. This is because, in 0.2-2% of cases, the escape of electrons from complex I (NADPH-dehydrogenase) and III of the electron transport chain occurring in mitochondria during ATP synthesis leads to the production of the superoxide radical anion (O2•−), which exerts detrimental intracellular effects owing to its high molecular instability. Along with ROS, reactive nitrosative species (RNS) also contribute to the production of free radicals. When the accumulation of ROS and RNS occurs, it can cause membrane lipid peroxidation and DNA damage. Here, we describe the intracellular pathways activated in brain tissue after a lethal/sub lethal ischemic event like stroke or ischemic tolerance, respectively, highlighting the important role played by oxidative stress and mitochondrial dysfunction in the onset of the two different ischemic conditions.